Formulation and In-vitro Evaluation of Baclofen Transdermal Patches - Sabati, Ahmed Mohmmed; Ali, Muaadh A. Mohamed; Ali, Bassam Abduh (BRNSS Publication Hub, 2017)
Aim: The aim of this study is to formulate and evaluate of baclofen transdermal patches using different polymers, penetration enhancers, and plasticizers. A drug with different film forming polymers was subjected to compatibility study. In addition, in-vitro permeation across animal skin for the best formulation was investigated. Materials and Methods: After studying the incompatibility of baclofen and other polymers used, the pure drug baclofen was formulated as transdermal patches composed of different polymers by solvent evaporation method and the formulations were 16. Then, the physicochemical properties of formulated patches were evaluated to determine the best optimum formula to be examined in-vitro release. Results and Discussion: The drug excipient compatibility study revealed no interaction between baclofen and polymers used. All the physicochemical studies of formulated patches were satisfactory except the formulation. The best-chosen formula was F13 that composed of polyvinyl alcohol as film-forming polymer and Carbopol 940 as bioadhesive polymer with propylene glycol as plasticizer and dimethyl sulfoxide as penetration enhancer. Conclusion: Study indicates that baclofen can be formulated as transdermal patches of acceptable appearance and suitable drug release through 24 h.